Clinical indicators for success of misoprostol treatment after early pregnancy failure - Robledo, C. (2007)
OBJECTIVE: To identify clinical indicators for success of misoprostol treatment after early pregnancy failure. METHODS: A total of 473 women with early pregnancy failure received 800 μg of vaginal misoprostol on treatment day 1. At the follow-up visit on day 3, a second dose was given if expulsion was incomplete. On day 8, vacuum aspiration was offered if expulsion had not occurred. Ultrasonography was used as gold standard for success. A Classification and Regression Tree analysis was undertaken to derive two decision trees for the success of misoprostol treatment on study days 3 and 8. RESULTS: Heavy bleeding after the first dose and an open cervical os were identified as clinical indicators of treatment success on day 3. Treatment success occurred in 84% of women with either or both indicators. Reporting passage of tissue after a second misoprostol dose and old blood in the vagina were potential indicators of treatment success or failure on day 8. A woman with either of these indicators has a 65% chance of treatment success after the second dose. Conversely, a woman with neither indicator on day 8 has a 94% chance of treatment failure. CONCLUSION: Standard clinical findings may be useful as indicators for success or failure of medical management of early pregnancy failure in settings with limited or no access to ultrasonography. More research to identify even better indicators is warranted.